Peran Kesiapan Belajar Online Sebagai Moderator Hubungan Antara Regulasi Diri dan Motivasi Belajar Praktikum Mahasiswa Selama Pembelajaran Praktikum Kimia Daring Di Masa Pandemi Covid-19 - Fazriyah, Latifatul; Khusrohmaniah, Sri (Jurnal Psikologi Perseptual, 2022)
Research has been conducted on the role of online learning readiness as a moderator of the relationship between self-regulation and student practicum learning readiness during online practicum learning during the COVID-19 pandemic. The purpose of this study was to determine the moderating role of online learning readiness on the relationship between self-regulation and practicum learning motivation. This research was conducted quantitatively on 147 students who had participated in online and face-to-face practicum learning in the laboratory (group 1; N=71), as well as students who only participated in online practicum learning (group 2; N=76). The results showed that online learning readiness had a significant moderating effect only in group 1, R2=38%; ∆R2 = 0,7%; F(3,91)=18,40; t(1,98)= -0,804; p0,05, while in group 2, the moderating effect were not significant, R2=6,1%; ∆R2=0,1%; F(3,91)=0,616; t(1,98)=0,237; p0,05. In group 1, students' practicum learning motivation decreased along with increasing self-regulation at all levels of online learning readiness, and in group 2 there was no moderating effect. That is, at each level of student online learning readiness, the higher the self-regulation, the lower the practicum motivation is. According to the results obtained, students' expectations, values, interests, and experiences related to practicum also affect the role of online learning readiness in moderating the relationship between self-regulation and student practicum learning motivation during online practicum learning during the COVID-19 pandemic.Telah dilakukan penelitian tentang peran kesiapan belajar online sebagai moderator hubungan antara regulasi diri dan kesiapan belajar praktikum mahasiswa selama pembelajaran praktikum daring di masa pandemi COVID-19. Tujuan dari penelitian ini adalah untuk mengetahui adanya peran moderasi dari kesiapan belajar online terhadap hubungan antara regulasi diri dan motivasi belajar praktikum. Penelitian ini dilakukan secara kuantitatif terhadap 147 mahasiswa yang pernah mengikuti pembelajaran praktikum daring dan tatap muka di laboratorium (kelompok uji 1; N=71), serta mahasiswa yang hanya mengikuti pembelajaran praktikum daring (kelompok uji 2; N=76). Hasil penelitian menunjukkan bahwa kesiapan belajar online memberikan efek moderasi secara signifikan hanya pada kelompok uji 1, R2=38%; ∆R2 = 0,7%; F(3,91)=18,40; t(1,98)= -0,804; p0,05, sedangkan pada kelompok uji 2 hasil moderasi yang diperoleh tidak signifikan, R2=6,1%; ∆R2=0,1%; F(3,91)=0,616; t(1,98)=0,237; p0,05. Pada kelompok uji 1 kesiapan belajar online memberikan moderasi negatif pada hubungan antara regulasi diri dan motivasi belajar praktikum, dan pada kelompok uji 2 tidak terjadi efek moderasi. Artinya, pada setiap tingkat kesiapan belajar online mahasiswa, semakin tinggi regulasi diri maka semakin rendah motivasi belajar praktikum. Menurut hasil yang diperoleh, harapan, nilai, minat, dan pengalaman mahasiswa terkait pelaksanaan praktikum juga berpengaruh terhadap peran kesiapan belajar online dalam memoderatori hubungan antara regulasi diri dan motivasi belajar praktikum mahasiswa selama pembelajaran praktikum daring di masa pandemi COVID-19.